1978
DOI: 10.1139/m78-185
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of staphylococcal thermonuclease (TNase) assay as a means of screening foods for growth of staphylococci and possible enterotoxin production

Abstract: Samples of food, naturally and artificially contaminated with Staphylococcus aureus, were analyzed for enterotoxin and thermonuclease (TNase). With the exception of egg, all naturally contaminated foods with detectable amounts of staphylococcal enterotoxin were positive for TNase. The enzyme was also present in the majority of foods with over 1 million S. aureus cells per gram. In artificially contaminated foods. TNase was detected in all samples except egg, acidic foods in which growth of S. aureus was suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Only one sample of raib contained more than lo4 S aureus/ml. All raib and jben samples were TNase-negative, indicating, therefore, the probable absence of staphylococci enterotoxins in these samples (Park et al, 1978;Tatini er al, 1975).…”
Section: Microbiological Characteristicsmentioning
confidence: 95%
“…Only one sample of raib contained more than lo4 S aureus/ml. All raib and jben samples were TNase-negative, indicating, therefore, the probable absence of staphylococci enterotoxins in these samples (Park et al, 1978;Tatini er al, 1975).…”
Section: Microbiological Characteristicsmentioning
confidence: 95%
“…Two studies [35,36] have shown that TNase is detected in most foods with S. aureus levels of more than 1 x 106 c.f.u./g. The absence of TNase in foods with high counts of S. aureus may be due to the presence of proteolytic enzymes originating from the S. aureus strain, from other organisms or from the food system itself [37,38].…”
Section: Thermostable Nuclease (Tnase)mentioning
confidence: 99%
“…(1) a high, but not complete, specificity (Bissonette et al 1980;Park et al 1980;Batish et al 1981, (2) interference due to inactivation by, for example, enterococci (Medwid & Grant 1980); and (3) no consistent quantitative relationship to staphylococcal colony counts (Park et al 1978;van 1984); Schouwenburg-van Focken et al 1978;Todd et al 1981;Stersky et al 1986).…”
Section: A a Mossel And P Van Nettenmentioning
confidence: 99%